Physician-patient communication: a qualitative study of perceptions, barriers, and needs in four European member states. (1st October 2020) - Dalma, Archontoula; Karnaki, Pania; Zota, Dina; Veloudaki, Afroditi; Ellis-Montalban, Paloma; Dotsikas, Kate; Christophi, Costas A.; Ioannidou, Eleni; Patouris, Eliza; Themistokleous, Sotiris; Batury, Victoria-Luise; Linke, Maike; et al.
ABSTRACT: Background: Good physician-patient communication is an important aspect of patient-centered care and contributes to positive health outcomes, however, there is a lack of standard European Union (EU) communication training policies for physicians. This study explores the barriers to good communication for both physicians and patients across four EU countries as part of the EU-funded project, Health Communication Training for Health Professionals – H-COM. Method: Focus groups were conducted with 31 patients and 38 physicians from Germany, Greece, Spain, and Cyprus. Two separate discussion guides were constructed for each target group around three themes: perceptions of, barriers to, and needs for health communication. Thematic analysis was used. Results: Commonalities and differences between countries and target groups were identified, with participants discussing attitudinal, emotional, educational, and systemic barriers to good communication. Participants indicated a significant gap in health communication knowledge, skills, and training for physicians, with regional differences. Conclusion: The results imply that there is a need for EU-wide communication training for physicians that would be best addressed by common themes and tailoring to specific regional differences. The results also imply that effective training should encompass a blend of theory and practical methods, and should be delivered via an e-learning platform for maximum accessibility. Training programs that adhere to these suggestions can begin to address the gaps in patient-centered care in the EU.